Traceability in continuous grinding circuits - Oghazi, Pejman (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2008)
Traceability is the means to identify and follow real or imaginary lots through a process chain. It gives the opportunity to back-track a chain of events, or to predict process outcomes given the origin of a lot. Traceability can be used in different areas, e.g., in the middle of 1990´s traceability was a hot subject when different cases of food-carried diseases were exposed, but traceability is also used in other process industries to follow material and products during the processing. There is, however, a lack of traceability in continuous processes to compared with batch processes; The reason is that it is more complicated to identify a lot, and reach good traceability, in continuous process just because of they are contiguous. In this work, an example is the continuous ore beneficiation process at LKAB (Luossavaara-Kiirunavaara AB, Sweden) Malmberget. The purpose is to trace the ore through the grinding sections by parameters and signatures like particle mineralogy, mineral associations and particle texture. To follow the material through the different process steps, analytical methods like optical microscopy and Particle Texture Analysis (PTA) are used In paper I, different traceability methods to achieve traceability in continuous processes are explained. The advantages and disadvantages are presented for each method. Paper II is showing the relations between the materials that comes into the grinding circuits. It also explains the PTA result, such as modal mineralogy, mineral liberation and mineral association. The feed and discharge for each mill is thoroughly investigated in this paper, which confirms that there are slight variations in results between section 5 and section 6. In paper III, data collected from the PTA analysis is subjected to multivariate data analysis. A multivariate model explaining the observations was developed. The results show that there are systematic variations in particle morphology along the process chain, but also between the grinding sections. The combination of automated ...